Multiple Identities as Reflected in English-Language Education: The Turkish Perspective - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2009)
Research on language and identity have generally been conducted in predominantly English-language native speaker settings, and results have revealed the language-learning process as a complex interplay of many variables in which social roles, relationships, and identities are constantly reconstituted. This study investigates how prospective teachers of English approach the issues of foreign-language learning and changing identities in an Islamic context, namely Turkey.
Keywords: identity; prospective EFL teachers; Islamic context; Western identity; TURKEY; INVESTMENT; CLASSROOM